Cornary microvascular dysfunction: an under- appreciatwed segment of coronary artery disease - Khaled, Md Fakhrul Islam; Banerjee, Sajal Krishna; Parvin, Tanjima; Adhikary, Dipal Krishna; Ahmed, CM; Siddique, Md Abu; Kabir, Mohammad Faisal Ibn; Hossain, Muhammad Mobarock; Rahman, Mohammad Abdur; Islam, Lohani M Tajul; et al. (University Heart Journal, 2015)
Abstract not available University Heart Journal Vol. 9, No. 2, July 2013; 107-111